Corporate social responsibility & the advertising strategic planning process: a literature review & research agenda. Issue 2 (17th February 2022) - Hayes, Jameson L.; Holiday, Steven; Park, Haseon
Abstract: Global consumers are increasingly expecting brands to strive to positively impact the communities and societies in which they exist. Marketers are taking heed, looking to balance social good against commercial profits in their decision making. Historically the purview of management, business ethics, and public relations research, advertising research has, until lately, largely ignored CSR and the critical role advertising communication and practice play in it. With CSR advertising scholarship on the rise, this article seeks to provide focus to the area by placing extant and future research in the context of the advertising strategic planning process (SPP) in order to holistically understand CSR's impact and gaps in knowledge. This study represents a systematic review of advertising CSR research in Social Science Citation Index advertising journals within the Web of Science database. Forty-three relevant articles were reviewed to identify relevance and situatedness within the SPP. Based on these findings, a research agenda addressing gaps in each of the stages of the SPP is proposed.